Prospective chemistry and science teachers’ metaphoric perceptions of science - (:unkn) unknown (Sakarya University, 2015)
The aim of this study is to determine freshmen and senior prospective teachers’ views of science by using their metaphors. Case study as a qualitative research design was benefited in the research. 145 prospective chemistry and science teachers from a university in İstanbul were participated in the study. Participants were asked to complete some sentences about science (science is like...;because...). The meaning of metaphor was briefly explained in order to guide the participants to construct relevant metaphors. The data of the study was analyzed with content analysis. It was found that prospective teachers constructed 69 different metaphors under 9 categories including “science is open to change”, “science is infinite”, “science combines different areas of studies together”, “science enlightens/guides people”. Among these, the most commonly constructed metaphors were sun (n=11), tree (n=11), light (n=10), ocean (n=7), space (n=7) and book (n=6). The findings of the study showed that most of the participants considered science as a tentative and infinite way. Some conclusions were discussed in the light of the findings. © The Turkish Online Journal of Educational Technology.